2003
DOI: 10.1007/bf02343533
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the influence of sports surfaces on vertical ground reaction forces during landing

Abstract: In many biomechanical analyses, the vertical ground reaction force (GRF) is measured by force plates. However, if force plates are fixed on elastic surfaces, the force signals have low-frequency oscillations superimposed. The question arises, as to whether this oscillation results from the response of the athlete to the surface properties or from the fixation of the force plate on the elastic surface. For the simulation of the vertical GRF, a mechanical model was developed that combines three submodels represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…1, adopted from [5]). By means of this model it is possible to simulate the gross movements of the jumpers as well as the small displacements of the concrete surface.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1, adopted from [5]). By means of this model it is possible to simulate the gross movements of the jumpers as well as the small displacements of the concrete surface.…”
Section: Methodsmentioning
confidence: 99%
“…After sometime the connection between the leg segments become more compliant and the jumper behaves like a four-mass model. Subsequently Fritz and Peikenkamp [5] combined the model of the jumper with submodels of the surface and the force plate. The simulations showed that, on the elastic wooden surface, the passive peak of the vertical ground reaction force (VGRF) was lower and was reached later than on the concrete surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The force platform in this study was fixed rigidly on the ground. This was necessary in order to ensure the movement was not affected by the platform, and to ensure a valid and reliable reading from the platform (Fritz & Peikenkamp, 2003). The best three data for peak VGRF were documented for each angle of squatting, thus the participants needed to perform at least three movements for each squatting angle.…”
Section: Demographics and Anthropometrics Datamentioning
confidence: 99%
“…48 Dance footwear ranges from dancing barefoot, in thin leather-soled ballet slippers lacking shock absorption, to high-heeled character shoes that prolong and increase loading on the female forefoot. 23,42 Hard floor surfaces increase shock attenuation demands on the feet, 21,61 while raked (inclined) stages are reported to be associated with 28% to 37% of all injuries. 18 Finally, females are at greater risk for stress fractures, 11 and the vascularity of their sesamoids is less extensive than that of males.…”
Section: Incidence and Etiologymentioning
confidence: 99%